Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

6(1 + 3R) = 2(10R - 9) -4R

Sagot :

Answer:

R=-12

Step-by-step explanation:

6(1 + 3R) = 2(10R - 9) -4R

Distribute 6 through the parentheses

6+18R=2(10R-9)-4R

Distribute 2 through the parentheses

6+18R=20R-18-4R

Collect like terms

6+18R=16R-18

Move the variable to the left-hand side and change its sign

6+18R-16R=-18

Move the constant to the right-hand side and change its sign

18R-16R=-18-6

Collect like terms

2R=-18-6

Calculate the difference

2R=-24

Divide both sides of the equation by 2

R=-12

if you'd make me brainliest that'd be great, if not its ok as well! I hope this helped!!!